2017
DOI: 10.1007/s11356-017-8543-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and microbial ecology of a paddy field after repeated applications of domestic and industrial sewage sludges

Abstract: The effects of repeated application of two types of sewage sludge, domestic and industrial (petrochemical, PSS) sludges, into paddy fields over a 5-year period on the soil properties and microbial ecology were studied and compared with conventional NPK fertilizer application. Soil organic matter and total nitrogen contents were significantly higher in the two sludge treatments than that in fertilized plots after 5 years. Soil concentrations of potentially toxic metals were low after 5 years of both sludge trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Segundo Matos (2014), dentre as vantagens que a compostagem pode trazer aos materiais submetidos ao processo, podem ser citadas: • Estabilização bioquímica, tornando-os isentos de maus odores e menos atrativo a vetores de doenças. (Liu et al, 2017;Sciubba et al, 2014). Essas mudanças podem ser associadas às mudanças nas capacidades funcionais das comunidades microbianas do solo (Fierer et al, 2012) que podem alterar a fertilidade e, como consequência, a produtividade agrícola nos solos receptores de composto.…”
Section: Fundamentos Do Processounclassified
“…Segundo Matos (2014), dentre as vantagens que a compostagem pode trazer aos materiais submetidos ao processo, podem ser citadas: • Estabilização bioquímica, tornando-os isentos de maus odores e menos atrativo a vetores de doenças. (Liu et al, 2017;Sciubba et al, 2014). Essas mudanças podem ser associadas às mudanças nas capacidades funcionais das comunidades microbianas do solo (Fierer et al, 2012) que podem alterar a fertilidade e, como consequência, a produtividade agrícola nos solos receptores de composto.…”
Section: Fundamentos Do Processounclassified
“…PLFAs allow distinguishing between bacteria and fungi, and further distinctions between bacterial groups such as Gram + and Gram − bacteria (Frostegård and Bååth, 1996). Other commonly used methods to determine changes in microbial metabolic diversity are community-level physiological profiling (CLPP) assays such as Biolog Ecoplates (Liu et al, 2017). The latter technique provides profiles of potential degradation of different complex chemical C substrates, which assess the ability of soil microbial communities to degrade natural soil constituents (Siebielec et al, 2018).…”
Section: Microbial Analysismentioning
confidence: 99%
“…When sewage sludge is not heavily polluted, similar trends can be observed (Table 7). Enzymatic activities have been shown to increase with the application of sewage sludge (Dar, 1996;Jorge-Mardomingo et al, 2013;Siebielec et al, 2018;Roy et al, 2019), soil microbial biomass (Charlton et al, 2016) and diversity indexes has been reported to improve based on Biolog assessments (Liu et al, 2017). DNA approaches have also revealed little effect on soil microbial diversity and bacterial antibioticresistance after the application of sludge (Rutgersson et al, 2020).…”
Section: Effects Of Dps Application On Soil Microbial Communitiesmentioning
confidence: 99%
“…In this condition, the farmers use the wastewater as irrigation water due to scarcity of freshwater and easy access . Soil fertility and crop production can be further improved by applying wastewater (Eid et al 2017;Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Uptake and accumulation of these metals inhibit plant growth and development and cause physiochemical responses . The bioavailability of PTEs depends on different factors such as the unique uptake mechanism of each of PTEs (Leuther et al 2019), plant growth stage (Qadir et al 2010), soil physical and chemical conditions (Liu et al 2017), sludge origin, and the concentration of toxic ions, and no particular pattern was noted for the transportation of PTEs inside of the plants (Leuther et al 2019).…”
Section: Introductionmentioning
confidence: 99%